Middle mesial canal in mandibular first molar: A narrative review - Raghavendra Penukonda; Harshada Pattar; Phrabhakaran Nambiar; Afaf Al-Haddad (Saudi Dental Journal)
Purpose: This review aimed to assess the incidence, anatomical characteristics, identification, and clinical management using conventional techniques and advanced tools to manage MMCs successfully. Methods: Medline/PubMed and Scopus databases were searched using “Middle mesial canal,” “Middle mesial root canal,” OR “Accessory mesial canal” keywords from 1 January 1970 and 1 February 2023. The most pertinent articles were chosen for the review from the retrieved articles. In addition, relevant articles were added by manually searching the list of references. Results: The incidence of MMC is noticeable in younger people, and the confluent canal is the most common type. The majority of MMCs merged with mesiobuccal (MB) canals rather than mesiolingual (ML) canals. Clinical management could be employed using the standard endodontics protocol, and recent radiography technologies, magnification, rotary, and obturation materials can facilitate the procedures. Conclusion: The possibility of the incidence of MMC is not unusual. Detection and thorough debridement followed by obturation of the canal could increase the success rate of clinical outcomes.